Health promoting pigments and bioactive compounds of six vegetables grown in Bangladesh - Sultana, Rowshon; Polash, Mohammed Arif Sadik; Sakil, Md Arif; Shorna, Shagata Islam; Rahman, Md Shahidur; Rahman, Md Atikur; Hakim, Md Abdul; Hossain, Md Alamgir (Asian Journal of Medical and Biological Research, 2020)
Increasing of chronic diseases due to low consumption of vegetables considered one of the crucial challenges to human being in current circumstance. Adequate intake of vegetables only the possible solution from get rid of the problem. So it is indispensible to determine food value present in vegetables which were the core objective of our present study. Among the tested vegetables beetroot showed the highest nitrate content (874 mg Kg-1) whereas the lowest nitrate content was found in bitter gourd (56 mg Kg-1). Total chlorophyll content was in cucumber, bitter gourd, beetroot, tomato and brinjal was 10 5.89, 4, 0.80 and 0.78 mg 100g-1, respectively. The highest carotene contain was found in cucumber (1.63 mg100g-1). Beetroot, tomato, brinjal and bitter gourd showed reduction in carotene content at 61.96, 71.16, 87.73 and 97.71%, respectively in response to cucumber. Lycopene content was the highest in beetroot (3.46 mg 100g-1) and the lowest in brinjal (0.115 mg 100g-1). All the tested vegetables contained abundance vitamin C (ranges from85.71 to 17.14 mg 100g-1). DPPH radical scavenging activity was present in all tested vegetables in which beetroot exhibited the highest DPPH radical scavenging activity with an IC50 value of 1.17 μgml-1. Asian J. Med. Biol. Res. June 2019, 5(4): 280-285